Family History of Alcoholism Is Associated With Lower 5-HT2A Receptor Binding in the Prefrontal Cortex - Underwood, Mark D.; Mann, J. John; Huang, Yung-Yu; Arango, Victoria (Alcoholism, clinical and experimental research, 2008)
Background:  5‐Hydroxytryptophan (5‐HT2A) receptor involvement in alcoholism is suggested by less 5‐HT2A binding in alcohol preferring rats, association of a 5‐HT2A receptor gene polymorphism with alcohol dependence and reduced alcohol intake with 5‐HT2A antagonists. We sought to determine postmortem whether 5‐HT2A receptors are altered in the prefrontal cortex (PFC) of alcoholics. Methods:  Brain tissue from 25 alcoholics and 19 controls was collected at autopsy. Diagnosis of DSM‐IV alcoholism/abuse and other psychiatric disorders and the determination of family history of alcoholism were made by psychological autopsy. Specific binding to 5‐HT2A (3H‐ketanserin) receptors in the PFC was measured by quantitative autoradiography. Results:  5‐HT2A binding decreased with age [Brodmann areas (BA) 9, 46 gyrus; r = −0.381, −0.334, p < 0.05]. No differences in receptor binding between alcoholics and controls were detected in the gyrus or sulcus of any PFC area examined. Cases (controls or alcoholics) with a family history of alcoholism (n = 23) had less 5‐HT2A binding throughout PFC than subjects without (n = 21) a family history of alcoholism (p < 0.05). 5‐HT2A receptor binding in alcoholics without a family history of alcoholism (n = 7) did not differ from controls without a family history of alcoholism (n = 14). There was no association between alcoholism or alcohol rating and genotype. There was an association between genotype and the total amount of 3H‐ketanserin binding in BA46 with the TT genotype having more binding (TT>TC≈CC). Conclusions:  Lower 5‐HT2A receptor binding in the PFC of cases with a family history of alcoholism suggests a genetic predisposition to alcoholism. Alcohol abuse by itself did not have a significant effect on PFC 5‐HT2A binding and as 5‐HT2A binding in alcoholics is not different from controls and antagonists may be therapeutic, fewer receptors may result in downstream developmental effects on the brain resulting in a predisposition to alcoholism.